The effect of Lee's strategy on critical thinking among primary school students in mathematics (Journal of the College of Basic Education, 2024)
The current research aims to identify (the effect of Lee’s strategy on critical thinking among primary school students in mathematics), The researcher followed the experimental method for its suitability to the research, The research sample included fifth-grade primary school students at (Asim bin Amr Al-Tamimi) school affiliated with the General Directorate of Education in Baghdad/Al-Karkh III in the academic year (2023-2024), with (69) students; Distributed into two groups (experimental and control) with (35) students in the experimental group and (34) students in the control group, The two groups were rewarded with variables (chronological age, previous achievement in mathematics, previous information in mathematics, and intelligence test), A critical thinking test consisting of (25) objective items was prepared, After correcting the test and analyzing the data statistically using the Spss program, The result of the research was that the students of the experimental group who were taught according to the (Lee) strategy excelled over the students of the control group who were taught according to the usual method in the critical thinking test, Based on this result, the researcher developed several conclusions, recommendations and proposals, It recommended conducting training courses for in-service mathematics teachers on applying the Lee strategy and how to employ it in teaching mathematics, And suggested conducting a study of this strategy on other dependent variables, such as scientific thinking, developing contemplative thinking, direction, and inclinations.